2015
DOI: 10.1155/2015/730407
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Adiponectin through 20-Year Type 1 Diabetes Duration

Abstract: Little information exists on the trajectory and determinants of adiponectin, a possible insulin sensitizer and marker for inflammation and endothelial function, across the duration of type 1 diabetes. The Wisconsin Diabetes Registry Study followed an incident cohort ≤30 years of age when diagnosed with type 1 diabetes during 1987–1992 up to 20-year duration. Adiponectin was concurrently and retrospectively (from samples frozen at −80°C) measured for those participating in a 20-year exam (n = 304), during 2007–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
3
2
0
Order By: Relevance
“…Overall, HbA1C was significantly correlated with TNF-α, but not in separate groups. These findings are similar to several previous reports [ 32 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, HbA1C was significantly correlated with TNF-α, but not in separate groups. These findings are similar to several previous reports [ 32 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the Wisconsin Diabetes Registry Study, the following conclusions were drawn: adiponectin level decreased with age, being more stable after the age of 20 years, females had higher adiponectin levels than males, and adiponectin was strongly correlated with waist circumference, weight, BMI, HbA1C, intensive insulin management, insulin pump use, and log insulin dose [ 32 ]. Adiponectin levels increased significantly following insulin therapy in the first five days and then had stabilized during the remission period in the third month after disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al (2000) reported that insulin increased NO production in cultured endothelial cells incubated with high-glucose conc., but this stimulatory effect of insulin is inhibited by hyperglycaemia. Several studies have been previously demonstrated that adiponectin level is higher in type 1 diabetic patients as compared to healthy control (Galler et al 2007;Maahs et al 2007;LeCaire and Palta 2015), which are in line of our findings. Again, insulin therapy reported a non-significant reduction in APN level.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed negative correlation between the serum levels of Adiponectin ng/ml and duration of disease/ year, this finding disagrees with the finding of Lindström et al who reported that the increase in circulating adiponectin concentrations in patients with type 1 diabetes appears to be strongly associated with long diabetes duration [34], however, in our study group the majorities of patients with long duration of diabetes are well-controlled patients. Our data showed that there was an inverse correlation between the level of serum adiponectin and BMI in type 1 diabetic children, many studies showed the same finding [31,35,36]. Decreased adiponectin levels was linked to Obesity after gender, age and diabetes were adjusted when compared to none obese patients [31,37], serum adiponectin level increases with weight reduction in both diabetic and healthy control individuals [38].…”
Section: Discussionsupporting
confidence: 68%